Fetal Alobar Holoprocencephaly - Maherunnessa,; Shermin, Shahana; Poddar, Hemonta (Delta Medical College Journal, 2025)
Alobarh holoprocencephaly is a very rare fetal congenital malformation. It is a disorder caused by the failure of procencephalon (forebrain) to sufficiently divide into the double lobed cerebral hemisphere. The result is a single lobed brain with skull and facial defects. Here we report a case of alobar holoprocencephaly detected by USG at 29 week of gestation though the routine 22 week anomaly scan was normal. She was counseled regarding the poor outcome of fetus with such disorder but she decided to continue the pregnancy up to term. She was admitted at her 38 weeks of pregnancy and delivered a male baby with congenital birth defects - alobar holoprocencephaly with cleft palate, cleft lip and absence of nasal bone. Delta Med Col J. Jul 2022;10(2): 83-86